Letter of condolence from Ilse Hochwald to Max Bredig, May 6, 1944 (1944)
Letter of condolence regarding the death of Georg Bredig (1868-1944) from Ilse Hochwald to Max Albert Bredig (1902-1977).
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Chemists; Condolence notes